Toksični vidiki galaktoze - je mleko res zdrava hrana v vseh življenskih pogojih? - Karas Kuželički, Nataša (Farmacevtski vestnik, 2008)
Milk is an important source of proteins and calcium in most Caucasian populations. However, the ability of milk ingestion in adults is quite an unusual occurrence, globally. In most mammals the activity of lactase decreases drastically after childhood. Subjects with partial galactose metabolism disruptions and high lactase activity in adult period, could be at the increased risk of some galactose toxicity related conditions such as cataract and ovarian cancer, especially if their milk ingestion is high.
Keywords: galaktoza; laktoza; mleko; rak (medicina); siva mrena